Dynamics and Limits of Regulatory Privatization: Reorganizing audit oversight in Russia. Issue 8 (August 2019) - Alon, Anna; Mennicken, Andrea; Samsonova-Taddei, Anna
Accounting and auditing are often cited as key sites where business regulation has been privatized, globalized and neoliberalized. Yet, these sites have also undergone a legitimacy crisis in recent years, marked by a shift from self-regulation to increased public oversight. This paper investigates these developments by reference to the evolution of a public/private audit oversight regime (audit of the auditors) in Russia. We show how, in the early stages of post-Soviet reforms, old state-administered forms of financial oversight were replaced with market-oriented arrangements (peer reviews) offered by newly founded private professional accountancy associations as a service to their members. Fifteen years later, the process of regulatory privatization culminated in a reinvigoration of public authority. Our longitudinal analysis highlights the pivotal role of the state in the liberalization of governance by showing how audit oversight privatization was not only enabled by, but also provided a condition for, the strengthening of government actors. We introduce the term 'legislative layering' to denote the mechanism that enabled public actors to redeploy themselves in the face of the rising market logic to ensure continuity in their regulatory objectives.